Design and syntheses of MOF/COF hybrid materials via postsynthetic covalent modification: An efficient strategy to boost the visible-light-driven photocatalytic performance - Li, Fei; Wang, Dengke; Xing, Qiu-Ju; Zhou, Gang; Liu, Shan-Shan; Li, Yan; Zheng, Ling-Ling; Ye, Peng; Zou, Jian-Ping (Applied catalysis. B, Environmental, 2019)
A novel strategy to fabricate hierarchical MOF/COF hybrids is proposed. For the first time, benzoic acid-modified covalent triazine-based frameworks (B-CTF-1) bonded with NH2-MIL-125(Ti) or NH2-UiO-66(Zr) via amide bonds are obtained. The resultant hybrid materials show superior photocatalytic activity and higher stability as compared to the simple heterostructures of MOFs and COFs connected via Van der Waals force. [Display omitted] •A novel strategy based on postsynthetic modification was proposed for fabrication of MOF/COF hybrids.•The as-prepared MOF/COF hybrids show superior photocatalytic performance of hydrogen evolution.•The role of as-formed amide bonds in MOF/COF hybrids was well investigated.•MOF/COF hybrids exhibit high stability and reusability during the catalytic reaction.•A mechanism for enhanced photocatalytic hydrogen evolution over MOF/COF hybrids was proposed. The search of novel visible-light-responsive porous materials is important because they hold great promise for applications in various fields. Herein, we report a novel strategy based on postsynthetic covalent modification for fabrication of hierarchical porous metal-organic frameworks/covalent organic frameworks (MOF/COF) hybrid materials. For the first time, benzoic acid-modified covalent triazine-based frameworks (B-CTF-1) are covalently bonded with MOFs (NH2-MIL-125(Ti) or NH2-UiO-66(Zr)) by using this strategy. Photocatalytic results show that the hydrogen production rate over 15 wt% NH2-MIL-125(Ti)/B-CTF-1 (15TBC) is 360 μmol·h−1·g−1 under visible light irradiation, which is more than twice as much as that of the B-CTF-1. Meanwhile, the hybrid materials show higher stability as compared to the simple heterostructures of MOFs and COFs connected via Van der Waals force. Photoelectrochemical analyses and controlled experiments indicate that the superior photocatalytic performance of the MOF/COF hybrids can be attributed to the formation of amide bonds between B-CTF-1 and MOFs, which facilitate the charge separation efficiency and improve the stability of the photocatalyst. Finally, a possible mechanism to well explain the improved photocatalytic performance of the photocatalytic system was proposed. The present work provides a new idea to construct highly efficient and stable MOF/COF hybrid systems and broaden the applications of COF-based materials.